Co-medications and Drug-Drug Interactions in People Living with HIV in Turkey in the Era of Integrase Inhibitors - Yeşilbağ, Zuhal; Şengül, Emine İlay and Şenoğlu, Sevtap and Aydın, Özlem Altuntaş and Karaosmanoğlu, Hayat K. (Current HIV Research, 2020)
Background: Long life expectancy in people living with human immunodeficiency virus (PLWH) caused an increase in comorbidities and co-medications. We aimed to analyse comedications and drug-drug interactions (DDIs) in antiretroviral therapy (ART)-naive PLWH in the era of integrase inhibitors. Methods: A retrospective observational study was conducted between January 2016-August 2019. Patients’ characteristics and chronic co-medications were recorded. The University of Liverpool HIV drug interaction database was used for DDIs. Results: Among 745 patients, the chronic co-medication rate was 30.9%. Older age (p<0.001, OR:6.66, 95% CI: 3.86-11.49) and female gender (p=002, OR:2.25, 95%:1.14-4.44) were independently associated with co-medication. Cardiovascular system (CVS) and central nervous system (CNS) drugs were the most common co-medications. Older age patients (p<0.001, OR:12.04, 95% CI:4.63-36.71), having heterosexual (HS) contact (p=0.003, OR:3.8, 95% CI:1.57-9.22) were independently associated with CVS drugs use, while being men who have sex with men (MSM) (p=0.03, OR:2.59, 95% CI:1.11-6.03) were associated with CNS drugs use. DDIs were seen in 37.4% of patients with co-medications. Antidiabetics (23.3%), CNS (22.1%) and CVS drugs (19.8%) most commonly had DDIs. Contraindication was most commonly seen between inhaled corticosteroids and elvitegravir/cobicistat. A number of non-ART drugs, elvitegravir/cobicistat, antidiabetics, vitamins were independently associated with the presence of DDIs. Conclusion: Results suggested the need for attention about co-medication in PLWH regardless of whether they are young or older. CNS drugs should be questioned more detailed in MSM, as well as CVS drugs in older HS patients. Elvitegravir/cobicistat is significantly associated with DDIs and switching to an unboosted INSTI should be considered in patients with multiple comorbidities.
Keywords: inhaled drugs